Pengendalian Hayati Patogen Fusarium oxysporum f. sp. capsici dengan Isolat Trichoderma sp. Asal Rizosfer Bambu dari Kecamatan Kedu, Kabupaten Temanggung - Sharfina Mutia Syarifah; Ofivah Permata Sari; Arif Bimantara (Institut Pertanian Bogor, 2024)
Wilt disease caused by Fusarium oxysporum f. sp. Capsici can cause serious problems and reduce red chili yields, so controls are needed that can reduce the development of the pathogen. The purpose of this study was to determine the potential of Trichoderma sp. from the bamboo rhizosphere in Kedu District, Temanggung Regency, in inhibiting the growth of F. oxysporum f. sp. capsici in vitro and in vivo. Trichoderma sp. Was isolated from the rhizosphere of bamboo plants, and F. oxysporum f. sp. capsici was isolated from red chili plants with symptoms of fusarium wilt. Mushroom isolates were purified and identified based on the identification key book. An in vitro test using the double culture method and an in vivo test were conducted in a screen house by applying Trichoderma sp. to the stem of red chili plants. One isolate of Trichoderma sp. was obtained from the soil of the bamboo rhizosphere in the Kedu District, and Fusarium sp. isolates were obtained from the stems of red pepper plants. Based on in vitro antagonist tests, Trichoderma sp. Fungi were able to inhibit the growth of F. Oxysporum f. sp. capsici up to 82.50% at 7 HSI. Trichoderma sp. could inhibit pathogens through antibiotic inhibition mechanisms and competition of nutrients and space to grow. Trichoderma sp. inoculation followed by in vivo inoculation of pathogens on red chili plant stems showed an attack symptom intensity of 4.16% with an antagonistic performance of 75.03% 12 days after inoculation. Trichoderma sp. is effective as an alternative biological control agent for red chili plant disease caused by F. Oxysporum f. sp. capsici. Keywords: Bamboo Rhizosphere, Fusarium oxysporum f. sp. capsici, Plant Diseases, Trichoderma sp.